Gender and start-up capital for agrifood MSMEs in Indonesia and Viet Nam - Ambler, Kate; de Brauw, Alan; Herskowitz, Sylvan; Murphy, Mike (International Food Policy Research Institute, 2020)
Micro, small, and medium enterprises (MSMEs) in developing countries frequently face financial con-straints undermining their ability to reach their full production potential. These constraints include expo-sure to uninsured risk, lack of suitable savings technologies, and expensive or inaccessible credit. Such challenges may be particularly acute for MSMEs operating in the agrifood system, in value chains be-tween farmers and retailers, where the seasonality and structure of these value chains creates unique financing needs relative to other sectors. Moreover, constraints affecting MSME performance in one part of the value chain may impact other value chain actors both up and downstream, including smallholder farmers, consumers, and exporters. As has been observed more broadly about MSMEs, marginalized groups such as women, low-income households, and ethnic minorities often face additional barriers to finance and adoption suitable financial services.1 If so, then the most vulnerable populations may be unintentionally excluded from emerging economic opportunities in the agriculture sector.